Judgments of damage to public versus private property in Chinese children at different historical times. Issue 1 (15th December 2016) - Chen, Xinyin; Li, Dan; Liu, Junsheng; Chen, Huichang; Zhao, Siman
Abstract: This study examined children's judgments of damage to public versus private property in China at two historical times. Participants were two cohorts (1980 and 2012) of elementary school children at ages 7, 9, and 11 years. The children were administered paired stories that described a protagonist who damaged public or private property with a good or bad intention. The results showed that children in the 2012 cohort were less likely than their counterparts in the 1980 cohort to judge damage to public property as more culpable than damage to private property. The cohort differences were more evident in older children than in younger children. The results suggest that macro‐level contexts may play an important role in shaping children's judgments. Abstract : The percentages of children in China judging the protagonist in the story damaging public property as more culpable were lower in the 2012 cohort than in the 1980 cohort. The cohort differences were more evident in older children than in younger children.